Clinical application of PEAK PlasmaBlade to remove distal tracheal granulation in patients after tracheostomy. Issue 1 (February 2022) - Lin, Wan-Ni; Hsin, Li-Jen; Fang, Tuan-Jen; Li, Hsueh-Yu; Li, Li-Ang
Abstract: Objective: Tracheal granulation is one of the common long term complications in patients after tracheostomy. Hypertrophic tracheal granulation may cause airway obstruction and further operation may be required to recreate an airway. Distal tracheal granulation is clinically challenging because of its position and surgical field limitation. This retrospective case review study evaluated the outcomes of PEAK PlasmaBlade-assisted tracheal surgery in patients with distal tracheal granulation. Methods: This study retrospectively reviewed patients with distal tracheal granulation following long-term tracheostomy. All patients received PEAK PlasmaBlade assistance tracheal surgery (PATS) between February 2013 and December 2019. The surgery was performed using the PEAK PlasmaBlade with TnA type tip, powered by a PULSAR Generator, and guided by a 45 ° rigid endoscope. Patients were regularly followed up for a minimum of 12 months. Results: A total 21 patients had completed PATS. None of the patients experience immediate life-threatening complications during or after the procedure. All the 21 patients were free of recurrent obstructive granulation within 12 months after operation. Conclusion: PATS is practical, effective, and safe for distal tracheal granulation and can be performed by single surgeon. Furthermore, it is technically less demanding than other surgical approaches and it has a rapid learning curve.